Hubungan Kekuatan Otot Lengan dan Bahu dengan Hasil Tolak Peluru Gaya O’ Brien Pada Mahasiswa Prodi Penjas Semester 5 Institut Pendidikan Nusantara Global - L. Hasan Ashari (Peneliti.net, 2021)
This research is correlational research penjas five semester student population. The sampling technique in this research by using total sampling, where samples performance this research is the population of 20 people.Instruments that do ntuk collect data in this research is to use the test and direct measurement explosive muscle power arm and shoulder with bullet style of reject O’Brien. Explosive muscle power measurement by using a medicine ball and shot put O’Brien style as much as 3 times. This study aims to determine how much information the relationship between explosive power arm and shoulder muscles with the results of shot put, as well as to determine whether there is any information about a meaningful relationship between the two variables.The data obtained as a result of the research is quantitative data through tests and measurements which will then be processed with statistical normality test done to test Liliefors at level α = 0.05. To find out how much the relationship between the two variables can be determined by using the product moment formula, whereas to find significant correlations can be determined by using t-test. Based on the research results, it can be concluded that there is a significant relationship between explosive muscle power arm and shoulder with the , bullet style of reject O’Brien, where the level of α = 0.05 obtained t 88,2 1.734 so t tabel Ho is rejected and Ha accepted, donations variable X the Y variables considered sufficient and obtained r = 0,98. variabel X terhadap variabel Y dikategorikan tinggi dan diperoleh rhitung = 0,98 >rtabel=0,444.